Rethinking the Re-Prep: Attitudes Toward Noninvasive Colorectal Cancer Screening Tests After Inadequate Bowel Preparation. (October 2019) - Platt, Kevin D.; Kurlander, Jacob E.; Zikmund-Fisher, Brian J.; Lipson, Rachel; Knaus, Megan; Waljee, Akbar K.; Saini, Sameer D.
Abstract : OBJECTIVES: To assess patient preferences for colorectal cancer screening with stool-based tests after initial colonoscopy with suboptimal bowel preparation. METHODS: An online scenario-based survey of adults aged 45 to 75 years at average risk for colorectal cancer was performed. RESULTS: When presented with a hypothetical scenario of screening colonoscopy with suboptimal bowel preparation, 59% of respondents chose stool-based testing as a next step, 29% preferred a repeat colonoscopy within a year, and 12% preferred a repeat colonoscopy in 10 years (N = 1, 080). CONCLUSIONS: Clinicians should consider offering stool-based screening tests as an alternative to repeat colonoscopy after suboptimal bowel preparation.